Prevalence of localized scleroderma in a specialized dermatology center in the State of Ceará, Brazil - Vale, Thais Campelo Bedê; Barros, Levi Coelho Maia; Lima, Matheus Eugênio de Sousa; Maia, Mariana Rocha; Aires, Maria Araci Pontes (Revista de Medicina, 2020)
Introduction: Scleroderma encompasses a broad spectrum of clinical manifestations, being subdivided into localized and systemic forms. The localized form exclusively affects the skin and surrounding tissues and has a partially known physiopathology and epidemiology, with the majority of epidemiological studies focusing on the systemic form and extrapolating its results to the other one. This study aim to clarify the epidemiology of localized scleroderma in the state of Ceará, Brazil, in order to understand its risk factors in the Brazilian population. This is the first Brazilian epidemiological study of localized scleroderma. Methods: A quantitative retrospective study was conducted, in which all the records of the medical consultations performed at the Reference Center for Dermatology Dona Libânia (CDERM), Fortaleza, Ceará, Brazil, in 2015 were analysed using the variables: name, gender, date of consultation, medical record number, presumptive or confirmed diagnosis and the patient’s frequency in CDERM. Results: Of the 19.576 patients analysed, 124 were diagnosed with scleroderma, representing an approximate incidence of 0.62% in the service. Among these patients, 96 (77.42%) were female and 28 (22.58%) were male. The mean age of the patients was 29.7 years. Discussion: Prevalence and distribution by sex obeyed the worldwide trends reported in other studies. However, there was a higher prevalence of diagnoses in females in the pediatric age group, which contrasts with data in the literature affirming that differences in gender distribution only begin in early adolescence. This difference may be due to cultural factors, underdiagnosis in the male population or a regional trend in the Brazilian epidemiology of localized scleroderma. Conclusion: More extensive and multicentric studies are needed to better understand the disease in our population and, thus, serve as a basis for healthcare in the future.